Lost in Translation: Problems of Rendering the Term Sustainable Development into Non-Western Languages as Demonstrated in the Case of South Korea - Baek, Kwang-Hoon; Ko, Nakil (Problemy Ekorozwoju, 2015)
This study seeks to demonstrate the usefulness of a relatively underutilized approach to studying sustainable development as a term and concept. While studies on sustainable development have generally followed a normative approach seeking what the term should ideally mean, this study follows a historical approach such as recommended by the historian of philosopher Quentin Skinner to explore what changes of definition it has been capable of undergoing in the actual use. To illustrate why such changes may be a critical issue, we have deliberately focused on the case of a country – South Korea – where the very translation of the term into the native language, combined with other factors, has resulted in sustainable development being generally understood by the public as meaning something quite different from the more normative understanding of the term. Instead of a balanced development that protects the environment and promotes social welfare as well as promoting economic growth, sustainable development in the standard Korean translation has come to be understood as simply meaning continued economic growth, which is to be sought even at the expense of environmental degradation. For documentation and analysis, we have relied on various methods, while focusing on key sectors and select policy areas, including energy. We conclude with further reflections on why an approach such as ours might be a useful methodological addition in sustainable development research.